Pengaruh Harga dan Ukuran Kemasan Terhadap Minat Beli Konsumen Pada Produk Es Teh Solo Jumbo - Nanda Angga Rizkita; Sopyan Imaduddin; Rizki Maulana; Faisal Tanjung; Wahyu Hidayat (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The competition in the beverage business is getting tighter along with the increasing activity of the population. One of the successful beverage products on the market is EsTeh Solo Jumbo. This iced tea is usually sold at an affordable price, which is around Rp3,000 to Rp4,000 per glass. In addition to its affordable price, Es Teh Solo also has a fairly large packaging size, so it is expected to be able to attract consumer interest. This study examines the effect of price and packaging size on consumer interest in Es Teh Solo beverage products. The research population consists of 40 people, all genders, who have purchased Es Teh Solo products. The data was obtained by distributing questionnaires to 40 Muslim students in Banten. Based on the research, consumer interest in Es Teh Solo has a positive and significant impact on price and packaging size.